Grid-scale energy storage systems and applications - Wu, Fu-Bao; Yang, Bo; Ye, Ji-Lei (Academic Press, 2020)
Grid-Scale Energy Storage Systems and Applications provides a timely introduction to state-of-the-art technologies and important demonstration projects in this rapidly developing field. Written with a view to real-world applications, the authors describe storage technologies and then cover operation and control, system integration and battery management, and other topics important in the design of these storage systems. The rapidly-developing area of electrochemical energy storage technology and its implementation in the power grid is covered in particular detail. Examples of Chinese pilot projects in new energy grids and micro grips are also included. Drawing on significant Chinese results in this area, but also including data from abroad, this will be a valuable reference on the development of grid-scale energy storage for engineers and scientists in power and energy transmission and researchers in academia.